On the phase and structural variability of directly injected propane at spark ignition engine conditions. (15th June 2018) - Poursadegh, Farzad; Lacey, Joshua S.; Brear, Michael J.; Gordon, Robert L.; Petersen, Phred; Lakey, Charles; Butcher, Brendan; Ryan, Steve; Kramer, Ulrich
Abstract: This paper presents an experimental and theoretical examination of directly injected (DI) propane at a wide range of conditions relevant to spark ignition engines. The investigated conditions comprise the injection of sub- and supercritical propane, with the latter representing a plausible, operational extreme during engine heat soak. Optical imaging is first used to study a wide range of observed spray behaviors, highlighting the sensitivity of DI propane to the engine operating condition. These varying behaviors then prompt further consideration of the thermodynamics involved. This extends thermodynamic arguments recently proposed by the authors in another work, and is able to explain when supercritical injection contains the liquid phase, when shock structures appear and when the spray collapses. Spray regime diagrams are then proposed in order to generalize the observed behaviors. These diagrams reveal several, often overlapping regimes that demarcate choked and unchoked injection, collapsed and multi-plume sprays, and the appearance or disappearance of the liquid phase immediately outside of the injector.